2000
DOI: 10.1126/science.287.5451.282
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Dietary Uptake and Reactive Sulfides on Metal Bioavailability from Aquatic Sediments

Abstract: Understanding how animals are exposed to the large repository of metal pollutants in aquatic sediments is complicated and is important in regulatory decisions. Experiments with four types of invertebrates showed that feeding behavior and dietary uptake control bioaccumulation of cadmium, silver, nickel, and zinc. Metal concentrations in animal tissue correlated with metal concentrations extracted from sediments, but not with metal in porewater, across a range of reactive sulfide concentrations, from 0.5 to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
201
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(213 citation statements)
references
References 18 publications
3
201
1
3
Order By: Relevance
“…Low BAFs values for this group of organisms could, therefore, be due the use of water and sediments data in computing BAFs. Similar results have been reported by Lee, B. G., et al [52] that most benthic organisms obtain a large fraction of their contaminants through ingestion and not by direct accumulation from overlying water or pore-water. Similarly, the BAFs for mercury in fish from coastal marine area of Tanzania were low and not significant.…”
Section: Mercurysupporting
confidence: 79%
“…Low BAFs values for this group of organisms could, therefore, be due the use of water and sediments data in computing BAFs. Similar results have been reported by Lee, B. G., et al [52] that most benthic organisms obtain a large fraction of their contaminants through ingestion and not by direct accumulation from overlying water or pore-water. Similarly, the BAFs for mercury in fish from coastal marine area of Tanzania were low and not significant.…”
Section: Mercurysupporting
confidence: 79%
“…Cd concentrations in nymphs were not directly related to those in either the sediment or the water of our study rivers, which suggests that both the bioavailability of metals in exposure media (Bryan and Langston 1992;Ankley 1996;Croteau et al 2002b) and the burrowing and feeding behavior of animals (Lee et al 2000;Wang et al 2001) need to be considered to relate metal concentrations in animals to those in their environs. The similarity in steady-state [Cd] between nymphs in containers and the environs suggests that bioavailable Cd concentrations in sediments were similar between the containers and their surroundings.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore applying this theory to metal remobilization studies would be proper only in the case that sulfides are not oxidized during elutriation (Di Toro et al, 1990;Durán et al, 2012). During the past years, much evidence has shown that benthic invertebrates can accumulate metals, even when [SEM]-[AVS] < 0, since benthic invertebrates ingest sediment particles as their main food source disregarding AVS (Lee et al, 2000a;Lee et al, 2000b;De Jonge et al, 2009;De Jonge et al, 2010). YHH3 YHH2 YHH1 GLH3 GLH2 GLH1 YHH-GLH ZMH2 ZMH1 ZM-YHH L1 L2 L3 L4 L5 MH6 MH5 XQH4 XQH3 XQH2 XQH1 K1 K2 K3 MH4 MH3 MH2 MH1 J1 J2 J3 J4 BLH3 BLH2 BLH1 I1 I2 I3 DH2 DH1 YH5 YH4 YH3 YH2 YH1 H1 H2 H3 WH3 WH2 WH1 JLH2 SEMs can be combined with AVS to reduce their toxicity; however, AVS of excessively high content is also harmful to aquatic organism.…”
Section: The Limitations Of Avs-sem Evaluation Methodsmentioning
confidence: 99%